Real-world experience on the safety and effectiveness of Micra TPS in patients with pre-existing in situ CIEDs. (14th October 2021) - Garweg, C; Bordachar, P; Boveda, S; Roberts, P.R; Johansen, J.B; Iacopino, S; Clementy, N; Winter, S; Anderson, C; Butler, K; El-Chami, M.F
Abstract: Background: The Micra pre-market study showed that the Micra transcatheter pacing system could be safely implanted in patients with pacing indications. Patients with pre-existing cardiac implantable electronic devices (CIED) were excluded from this clinical trial; however, this group of patients might benefit from a leadless pacemaker especially when a lead fails or after incidence of system-related infections. Objective: To determine the outcome of patients with a pre-existing CIED or lead that remains in situ at the time of Micra implant attempt. Methods: Patients who had a pre-existing CIED and/or lead at the time of Micra implantation attempt were identified from the Micra Post-Approval Registry and Micra Acute Performance studies. Baseline characteristics were summarized, and a Fine-Gray competing risk model was used to compare risk for major complication through 24 months for patients with and without a pre-existing CIED. Results: Of the 2323 patients included in the analysis, 111 patients had a pre-existing CIED or lead at the time of Micra implantation attempt that remained in situ. Types of pre-existing devices included 81 pacemakers (45 single chamber, 32 dual chamber, 4 of unknown type), 10 ICDs (2 single chamber, 2 dual chamber, 6 unknown type), 10 CRT devices (6 CRT-P, 4 CRT-D), 3 generators of unknown type, and 7 patients had only leads remaining. Patients with pre-existing devices were younger and less likely to have a pacing indication of bradyarrhythmia with atrial fibrillation compared to patients without pre-existing devices (p<0.001 for both). Patients with prior devices were more likely to have a condition precluding implant of a transvenous pacemaker (67.6% vs. 21.3%, p<0.001). The presence of a pre-existing CIED did not impact the outcome of the Micra TPS implant procedure: implant success was >99% for both cohorts. Mean follow-up duration was 21.2±14.3 months (range 0–56) for pre-existing devices patients and 23.3±15.8 months (range 0–62) for other patients. The rate of major complications through 24 months was 1.8% for patients with and 3.8% for patients without prior devices (p=0.36). There were no major complications related to device malfunction or device-device interaction. There were 6 system revisions in 4 patients with preexisting devices and 52 revisions in 51 patients without preexisting devices. Pacing thresholds for patients with and without prior devices were similar at implant (0.72 and 0.63, respectively; p=0.31) and remained stable through 12 months. Conclusion: Micra can be safely and successfully implanted in patients with a pre-existing CIED remaining in situ. It should be considered a treatment option for patients in whom CIED extraction may be deemed high risk. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Medtronic, Inc.